New combinations in Ruehssia for the South American species of Marsdenia (Apocynaceae-Asclepiadoideae) - Liede-Schumann, Sigrid; Keller, Héctor A. (Phytotaxa, 2020)
The South American species of Marsdenia are transferred to Ruehssia, following the recognition of this lineage as independent from Marsdenia s.str. New combinations are provided for 22 species and 2 subspecies; eight names are lectotypified, and one is neotypified.